Working Memory Deficits in Multiple Sclerosis: An Overview of the Findings - Kouvatsou, Zoe; Masoura, Elvira; Kimiskidis, Vasilios (Frontiers in Psychology, 2022)
Although Working Memory and Information Processing Speed impairments in Multiple Sclerosis have been widely investigated, several questions, regarding the nature of these impairments and their relationship, remain unclear. The aim of this short communication article is to present our research findings regarding a) the characteristics of Working Memory impairment in Multiple Sclerosis patients and, more precisely, the degree of impairment observed in each Working Memory’s component, i.e. phonological loop, visuospatial sketchpad, central executive and episodic buffer, and b) the relationship between Information Processing Speed and each of the four Working Memory components, in an attempt to expand the existing rather narrow understanding of the interconnection between reduced Information Processing Speed and Working Memory impairment. Two studies of our research team are presented here and their findings are briefly discussed, highlighting the importance of further research on a specific component, namely the episodic buffer component among Multiple Sclerosis patients.